2020
DOI: 10.3389/fpsyt.2020.573367
|View full text |Cite
|
Sign up to set email alerts
|

Effectively Caring for Individuals With Behavioral and Psychological Symptoms of Dementia During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has significantly affected the elderly and particularly individuals with Alzheimer’s disease and related disorders (ADRD). Behavioral and psychological symptoms of dementia (BPSD) are heterogeneous and common in individuals with ADRD and are associated with more severe illness. However, unlike the cognitive symptoms of ADRD that are usually progressive, BPSD may be treatable. Individuals with BPSD are facing unique challenges during the pandemic due to the inherent nature of the illness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 88 publications
(90 reference statements)
2
68
0
1
Order By: Relevance
“…6,7,9,17,18,20 Worsening symptoms may be due to lack of mental stimulation as well as disrupted daily routines. 20,32 Cancellation of recreational activities or reduction of visits from family or friends due to COVID-19 can negatively influence PLWD. 32 Taking care of PLWD with worsening symptoms might have caused stress and anxiety in the dementia caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,9,17,18,20 Worsening symptoms may be due to lack of mental stimulation as well as disrupted daily routines. 20,32 Cancellation of recreational activities or reduction of visits from family or friends due to COVID-19 can negatively influence PLWD. 32 Taking care of PLWD with worsening symptoms might have caused stress and anxiety in the dementia caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…In an ecological study by Azarpazhooh et al (31), healthy life-expectancy and dementia disability adjusted life years (DALY) were significantly related to the COVID-19 caseloads and mortality. Studies have also shown significant impact of COVID-19 related lifestyle changes, social isolation, loneliness and quarantine measures on the behavioral and psychological symptoms of dementia (BPSD), especially sleep disturbances, anxiety, depression, agitation and wandering (32,33)…”
Section: Potential Worsening Of Dementia With Covid-19 Infectionmentioning
confidence: 99%
“…A significant interaction between the nursing home residence variable and dementia in COVID-19 patients was observed. The results can be potentially explained by a higher exposure and infection risk of demented nursing home residents caused by a lower ability to adhere to the needed isolation behaviors (68). COVID-19 exposure in nursing home has been reported by others and is a common issue in several countries (24,69).…”
Section: Discussionmentioning
confidence: 83%